Acrachemmics (Acid Rain in Chemical Comics) Oriented to Chemical Literacy - Rifa Khaerunnisa; Ferli Septi Irwansyah; Citra Deliana Dewi; Iis Dahriah; Yana Aditia Gerhana (Online Learning In Educational Research (OLER), 2025)
Understanding chemical concepts such as acid rain can be challenging for students due to their abstract and complex nature. To address this, a chemical literacy-based learning approach using comic media. Acrachemmics (Acid Rain in Chemical Comics) was developed to enhance student comprehension. This research aims to develop and evaluate electronic comic media especially Acrachemmics (Acid Rain in Chemical Comics). A Design-Based Research (DBR) methodology was employed, comprising three phases: analysis, design, and development. The validation test yielded a Pearson correlation coefficient (r) of 0.88, indicating a high level of content validity. Additionally, the feasibility assessment, which examined aspects of material content, visual communication, software engineering, and language, produced an average score of 84 percent, reflecting a high level of practical usability. These results suggest that Acrachemmics is both a valid and feasible educational media for teaching acid rain concepts. By presenting scientific content through engaging visuals and narrative storytelling, Acrachemmics facilitates student understanding in a more accessible and enjoyable format